Students' abilities and attitude as correlates of achievement in senior secondary school physics in Bayelsa state: A study in school effectiveness (2010)
Students' achievement is one of the measures of school effec tiveness; schools have been labelled ineffectiveness because of poor achievement of students in school subjects like physics both at school and public examinations. This poor performance has been a concern to science educators and the society because of the importance of the subject. The failure rate may be due to studetns' abilities and attitude to the subject. This study, therefore, the study examined the composite and relative contributions of three personalitity variables(students' reasoning ability, mathemtical ability and studetns' attitude to physics) to students' achievement in physics. The study adopted a survey research of the expo facto type. A multisatge sampling techniques was employed to obtain a sample of 225 senior secondary three students from three educational zones in souther Ijaw local government. Two instruments used in this study were the Students Questionnaires (SQ) and Physics Achievement Test (PAT). The data collected were subject to parcentages and mulitple regression analysis at p <0.05. The combination of the predictor variables students' reasoning ability and attittude explained 90.5 percent of the varience in students' achievement in physics as shown by the coefficeient of determination (R2=0.905). The relative contributions of each of the three studetns predictor variables shows that studetns' reasoning ability had the highest contribution of (β=0.355, p<0.05) on studetns' achievement in physics, followed by the students'attitude, which had a relative contribution of (β= 0.274, P<0.05) contribution to students' achievement in physics. The standardized regression associated with each variable reveals the order of contribution as follows reasoning ability > attitude> mathematical ability.The potent predictor variables to student's reasoning ability. Therefore, physics teachers should in corporate high order cognitive skills into demostration classes such that activities therein are tailored to develop critical thinking skills.